Meister Eckhart (1260-1327) or the “secularization” of christian mystic experience - Maestre Sánchez, Alfonso (Anales del Seminario de Historia de la Filosofía, 2007)
Since the thirteenth century it is possible to talk about “secularization” of the mystic experience that led to a new stage in the history of the Christian mysticism. Meister Eckhart can be undoubtedly considered as an exceptional theologian who proclaims and justifies, theologically, the possibility of reintegrating the ontological identity with God without the necessity to leave the world. With his own life and instructions, he made possible that true contemplation was a Christian action. This Chistian action arises as a contemplative style of life